Optimasi Konsentrasi Induser Galaktosa pada Produksi Endo-Β-1,4-D-Xilanase di Escherichia Coli BL21 (DE3) (XynBTN63D) Menggunakan Media Terdefinisi Trace Elements (MTE) Dalam Bioreaktor - Emilia Rohmawati (Fakultas Matematka dan Ilmu Pengetahuan Alam, 2025)
Endo-β-1,4-D-xylanase from Escherichia coli BL21(DE3) (XynBTN63D) functions as a catalyst in the hydrolysis of xylan into xylooligosaccharides, which possess prebiotic properties. However, the production of this enzyme commonly relies on Luria Bertani (LB) medium and the costly inducer IPTG, making it less economical for industrial-scale applications. Therefore, this study aimed to evaluate the effectiveness of galactose as an alternative inducer and the use of a defined trace element (MTE) medium for producing XynBTN63D in a 1-L stirred tank bioreactor. Enzyme production was carried out using varying galactose concentrations (40, 45, 50, and 55 mM), followed by determination of enzyme activity against xylan and synthetic substrates (pNP-A and pNP-X), analysis of total protein content, protein expression via SDS-PAGE, and characterization of hydrolysis products using thin-layer chromatography (TLC). The results showed that 50 mM galactose yielded the highest specific activity against beechwood xylan (1.078 U/mg) and pNP-A (8.069 × 10⁻³ U/mg), while 45 mM galactose produced the highest specific activity against pNP-X (7.938 × 10⁻³ U/mg). These findings suggest that galactose, particularly at 50 mM, has strong potential as an effective alternative inducer to IPTG for the production of XynBTN63D.
Reuploud Repository hasyim Mei 2026 Approved by Teddy
Keywords: XynBTN63D; Endo-β-1; 4-D-xylanase; Galactose; Induction of gene expression; Defined medium (MTE)